Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1111/j.1753-6405.2010.00600.x
|View full text |Cite
|
Sign up to set email alerts
|

Poor uptake of self‐sample collection kits for Chlamydia testing outside primary care

Abstract: Objectives: New strategies are needed to reach at-risk populations for Chlamydia screening.Method: Self-sample collection kits containing instructions and all items required for testing were developed and piloted in a three-month trial in primary care.Practice staff offered kits to young people receiving opportunistic Chlamydia screening to pass on to their 'social contacts.' Results:The 'pass it on' approach failed to reach adequate numbers of youth for testing: of 67 kits distributed, three specimens were se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Four programs involved study personnel directly inviting people to receive PTKs and were based in England [52,54], Australia [53] and New Zealand [55] (Table 3). Two programs were in pharmacies [52,54], one in general practice [55] and one at a music festival [53].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four programs involved study personnel directly inviting people to receive PTKs and were based in England [52,54], Australia [53] and New Zealand [55] (Table 3). Two programs were in pharmacies [52,54], one in general practice [55] and one at a music festival [53].…”
Section: Resultsmentioning
confidence: 99%
“…Two programs were in pharmacies [52,54], one in general practice [55] and one at a music festival [53]. A total of 341 tests were conducted (median: 37).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several innovative peer-led intervention programs aiming to reach high risk social and sexual networks have been developed using home-collection and/or e-health technologies [ 34 37 ]. Moreover, a few studies have assessed peer-led CT screening using home-based testing [ 33 , 38 , 39 ]. Loaring et al .…”
Section: Introductionmentioning
confidence: 99%
“…[ 33 ], showed that in a small study of 12 women and men, women were potentially more willing to provide their social network with test kits, yielding 34% of kits returned by peers for testing. This peer test return rate was 26% for the sexual partners of 637 diagnosed CT positive persons (general practitioner care) in a study by Ostergaard et al [ 38 ], while it was only 4.5% for social peers from 67 indices tested in a primary care setting in a study by Rose et al [ 39 ].…”
Section: Introductionmentioning
confidence: 99%